Improving the Reach of the National Diabetes Prevention Program Within a Health Disparities Population: A Bronx New York Pilot Project Crossing Health- and Community-Based Sectors. Issue 4 (2016) - Morrow, Robert; Ferretti, Lisa; Norwood, Chris; Reich, Douglas; Chito-Childs, Erica; McCallion, Phillip; Tiburcio, Jose; McGee, Eleanor; Lopez, Jose A.
Abstract : Introduction: Diabetes affects upward of 30% of South Bronx residents. The Centers for Disease Control and Prevention's National Diabetes Prevention Program (NDPP) reduces risk of progression to diabetes, yet implementation has been elusive within health disparities populations. Methods: This community-based, collaborative project piloted the NDPP in the South Bronx and evaluated implementation challenges and enablers. The New York State training group prepared community peer lifestyle coaches recruited by a community organization. A professional society trained academic detailers from local faculty. An interview process evaluated community needs and public health officials' beliefs. A portal managed by the New York State training group collected demographic and biometric data from the community participants and facilitated online registration. Data from interviews and observations were coded systematically using a thematic analysis framework. Results: We were successful at recruiting and training 14 lifestyle coaches and 7 academic detailers, as well as recruiting members of the health disparities population in the South Bronx into the program. Fifty-two individuals completed the first 6 months of the yearlong program, attending an average of 12.7 of 16 sessions. By week 16, weight loss averaged 7.4 lbs and many had doubled their minutes of physical activity. Local electronic referral and feedback systems were developed. Discussion: Health professionals, their teams, public health centers, and communities can work together to prevent diabetes by enhancing the reach of the NDPP to health disparities populations. Peer education using lifestyle coaches can provide a trustworthy process for crossing the boundaries between health teams and community support groups.